What Motivate Muslim Consumer to Patronage Islamic Based–Retail Store? - Waida Irani Mohd Fauzi; Nazlida Muhammad; Sany Sanuri Mohd Mokhtar; Rushamie Zain Yusoff (International Review of Management and Marketing, 2016)
There is a significant trend among Muslim consumers in reverting to Islamic way of life. The phenomenon somehow affected the Malaysian retail industry with specialty Islamic stores mushrooming, and retailers customizing retail elements to win the Muslim consumers segment. As the mainstream studies on retailing acknowledges the adaptation of retail elements to suit consumers’ segment, there are less report on customizing retail elements to religious consumer group such as Muslim consumers’ segment. Thus, little is understood of consumers’ patronage motives and their expectations of retail Islamic stores. The aims of this study are twofold: to explore Malaysian Muslim consumers’ expectations of Islamic-based retail store; and their motive to patronize an Islamic-based retail store. Findings from interviews, conducted in the Northern region of Malaysia, suggest unique religion-related patronage motives. This study shares some initial insight into criteria for Islamic retail-based segmentation for Muslim consumers. Implications and limitations of the study are also discussed.